ELECTRONIC TRASH: ASSESSMENT AND AWARENESS OF THE URBAN AREAS OF FREDERICO WESTPHALEN AND TAQUARUÇU DO SUL - Weiler, Elenice Broetto; Hedlund, Keila Fernanda Soares; Lambrecht, Fernanda Raquel; Silva, Tainara Casa Nova; D’avila, Marcia; Torres, Oscar (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The objective of this work was to evaluate the level of awareness of students, traders and consumers regarding the use and appropriate disposal of electronic waste, as well as raising awareness of the question to the target public. The study was conducted in the urban areas of FredericoWestphalen and Taquaruçu do Sul, Rio Grande do Sul State, Brazil, where applied an average of 2,000 files in schools covering at 10 schools, and in every city an average of 10 questionnaires for stores linked to or bouquet of household appliances and electro-electronic, totaling 50 local.After this task was to analyze the dates obtained, which formed the basis for the development of the talks also took place in the schools of those cities.With the results we observe a absence of information on the topic electronic trash, requiring, therefore, specific knowledge to assist students on environmental issues. The process of developing and delivering lectures in schools was very positive; yielding a good response from students who were moved with the reality exposed to them, and also showed interest in divulging it. The traders welcomed the proposal of awareness and planned to pass the folders that were made for better disclosure of the question in society